Effect of Crude Oil Prices on Economic Growth in Kenya in the Period 1981 To 2018 - ONONO, PEREZ; Mutuma Kiambi, Benedict; Maingi, James (Advances in Social Sciences Research Journal, 2020)
Crude oil is an essential resource in the day-to-day activities of a functional economy. Crude oil and petroleum products constituted 14 percent of the Kenya’s imports in 2017 up from 12 percent in 2015. As Kenya moves into an oil-exporting country, there is a need to measure the role crude oil prices play in directing the economic growth of the country. This study assessed the effect of crude oil prices on the economic growth of Kenya. Gross capital formation, bank lending rate, employment rate and debt servicing were used as control variables in the models estimated. The study employed secondary data for the period 1981 to 2018. The findings indicate that crude oil prices had a positive but insignificant effect on economic growth. The study recommends that the government diversifies its sources of energy to ensure that economic activity economy is not deeply connected to crude oil prices because of their volatility.